Estimating residential CO2 emissions based on daily activities and consideration of methods to reduce emissions. (July 2016) - Hirano, Yujiro; Ihara, Tomohiko; Yoshida, Yukiko
Abstract: To achieve a low-carbon society, it is crucial to make the transition away from wasteful lifestyles that are shaped by mass production/mass consumption towards low-carbon lifestyles. Research in the field of urban environmental studies examining human behavioral factors affecting energy consumption, has mostly focused on CO2 emissions relating to direct energy consumption, such as the use of air conditioners and water heaters. As CO2 emissions from the industrial sector are greater than those from the residential and transportation sectors in Japan, it would be prudent for consumers to work on reducing CO2 emissions relating to products and services. In an effort to provide some basic research to achieve the aforementioned objectives, this study looked at statistical data from sources such as the Japanese Family Income and Expenditure Survey and the Japanese National Survey of Family Income and Expenditure to estimate direct and indirect CO2 emissions relating to daily expenditures and consumption. As a case study, we selected a sample denizen to calculate the CO2 emissions relating to daily living. Based on the obtained results, we examined the lifestyle and consumption patterns and their relation to CO2 emissions. The results suggest that while it is still important for consumers to reduce their direct energy consumption in an effort to create a low-carbon society, there is still potential for indirect CO2 emission reductions in areas of production and consumption. Highlights: Lifestyle-generated direct/indirect CO2 emissions in Japan have been estimated. Direct CO2 emissions were estimated to be approximately 4.9 [kg-CO2 /person/day]. Indirect CO2 emissions were estimated to be approximately 5.1 [kg-CO2 /person/day]. As a case study, CO2 emissions at the individual level were estimated. The results showed that there is a large potential to reduce indirect CO2 emissions.